Travelling abroad with cystic fibrosis: Assessment of risks and healthcare requirements. (April 2017) - Miller, Rachel; Blanch, Laura; Lenaghan, Sarah; Anderson, Alan; Doe, Simon; Bourke, Stephen J.
Abstract: There is limited information on the risks and healthcare requirements of patients with cystic fibrosis (CF) undertaking travel abroad. Of 100 patients (mean age 24.7 years, mean FEV1 57.3 %predicted) attending a UK adult CF Centre, 96% had travelled abroad but 14% now limited travel on medical advice. They travelled frequently and widely, often undertaking adventurous activities on holidays, but because of the costs involved, 18% travelled without travel insurance and 23% with insurance which did not cover CF. Of those who had ever had an illness abroad 10% had a CF-related illness (7 chest infection, 2 dehydration, 1 pancreatitis) and 12% a non-CF-related illness (4 sunburn, 3 gastroenteritis, 3 ear infection, 1 fall, 1 gastro-oesophageal reflux). There is a wide range of disease severity and assessment of the medical risks and the travel insurance premium to be charged should be based on the individual's health status rather than generically on the basis of a diagnosis of CF. Highlights: People with CF are travelling abroad frequently and undertaking diverse activities. In those travelling with the support of their clinical team travel is generally safe with few serious problems. Assessment of risks and travel insurance premiums should be based on their current health status.